Designing Learning Media Using Augmented Reality for Engineering Mechanics Course - Fortuna, Aprilla; Waskito; Purwantono; Kurniawan, Andre; Andriani, Welli; Alimin, Masnaini (Researcher and Lecturer Society, 2023)
The development of digital technology for education is continuously conducted to successfully integrate digital technology with people's lives. This study aimed to develop an Augmented Reality learning media application for the Engineering Mechanics course, which is considered challenging by some students. Engineering mechanics, a discipline that analyzes structural analysis in compensating for the loads that work on a particular machine in scalar quantities, motion forces, vectors, and moments that require physical structural forms to analyze them, is considered challenging by some students. The Augmented Reality application was created using the prototyping method, which consists of three steps: 1) listening to the customer, 2) building/ revising mock-up, and 3) customer test-drivers mock-up. The AR-based learning media application includes usage instructions, developer info, learning videos, 3D AR object animation simulations, and exercise and discussion menus, which were tested as expected. The results of the black box testing indicate that the Augmented Reality-based engineering mechanics learning media application ran successfully as expected. However, users suggested improving the navigation speed by streamlining page transitions. The application provides an accessible solution for students as an alternative to traditional distance education, offering anytime, anywhere access to learning materials with longer duration.